Naturkatastrofer i menneskets tidsalder - Ekström, Anders; Svensen, Henrik H. (Tidsskrift for kulturforskning, 2014)
Since the early 2000s, the Anthropocene has gained momentum as a new geological and historical epoch defined by the pervasive human influence on Earth systems. The anthropocene concept is widely used both in the scientific literature and elsewhere. The idea of an Age of Man changes our understanding of the relationship between natural and cultural processes and how different societies are interconnected across time and space. One of the challenging aspects of the anthropocene concept is the consequences for the understanding of natural disasters. Traditionally, natural disasters developed along the nature-society interface where the severity depends on the magnitude of the natural hazard and the human vulnerability. However, within the anthropocene framework, natural hazards can be understood as hybrid processes partly controlled by the human influence on Earth systems. The best examples of such hybrid processes are within the climate-related hazards such as heatwaves and floods.